'Breeders for race and nation': gender, sexuality and fecundity in post-war British fascist discourse. (8th August 2021) - Burnett, Scott; Richardson, John E.
ABSTRACT: Burnett and Richardson's paper has two related aims. First, it develops a model of how gender is articulated within fascist and other far-right discourses based on a review of the relevant scholarship. This model is presented in the first section. Researchers have in the past suggested a gap, or even a wilful ignorance, of gender in studies of the far right, and claimed that the topic is 'neglected' and 'under-researched'. This gap is to some extent held open by disciplinary, historical and definitional boundaries that work fractally to split inquiry. Burnett and Richardson have thus read the literature in a kaleidoscopic fashion, including analysis across different historical periods and country contexts, to examine how gender surfaces in various 'fascist' discourses. This approach covered psychoanalytical, discourse analytical, historical, art historical, literary, political and anthropological approaches to gender and fascism. The second aim of the paper is to show how the model proposed is brought into relief in a particular country context: that of the United Kingdom since the Second World War. Gender in post-war British fascism has been the subject of several important studies, though none of them have specifically traced the textual journey of key ideas and themes related to gender in mediatized far-right discourse. Building on a discourse-historical analytic approach to the development of fascist politics of this period, Burnett and Richardson argue that paying attention to gender in fascist discourse is a useful lens through which to analyse the local and historical contingencies that make one fascist discursive formation differ from another.